2012
DOI: 10.1121/1.4747614
|View full text |Cite
|
Sign up to set email alerts
|

Intelligibility of whispered speech in stationary and modulated noise maskers

Abstract: This study investigated the role of natural periodic temporal fine structure in helping listeners take advantage of temporal valleys in amplitude-modulated masking noise when listening to speech. Young normal-hearing participants listened to natural, whispered, and/or vocoded nonsense sentences in a variety of masking conditions. Whispering alters normal waveform temporal fine structure dramatically but, unlike vocoding, does not degrade spectral details created by vocal tract resonances. The improvement in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
39
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 38 publications
7
39
1
Order By: Relevance
“…Based on their results, these authors concluded that the MR observed for TFS speech may arise from the use of RENV rather than TFS. This observation agrees with recent studies that question the role of TFS cues for aiding in speech perception in the presence of fluctuating interference (Oxenham and Simonson, 2009;Freyman et al, 2012).…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Based on their results, these authors concluded that the MR observed for TFS speech may arise from the use of RENV rather than TFS. This observation agrees with recent studies that question the role of TFS cues for aiding in speech perception in the presence of fluctuating interference (Oxenham and Simonson, 2009;Freyman et al, 2012).…”
Section: Introductionsupporting
confidence: 82%
“…However, the importance of TFS cues for "listening in the gaps" has been called into question by several studies exploring this hypothesis (Oxenham and Simonson, 2009;Freyman et al, 2012). For example, Oxenham and Simonson (2009) did not find a greater MR for low-pass filtered speech (which would contain TFS cues) compared to high-pass filtered speech (where TFS cues for resolved harmonics would be absent).…”
Section: Masking Releasementioning
confidence: 93%
See 1 more Smart Citation
“…It has been proposed that TFS cues may be important for the perceptual separation of target speech from interfering sounds (Hopkins and Moore 2011;Moore 2014) and may underlie the ability to take advantage of the energetic minima in fluctuating background sounds, so-called dip listening (Lorenzi and Moore 2008). The latter proposal is however contradicted by studies showing that dip-listening performance for speech in noise is similar for speech containing strong or intact TFS cues and speech containing weak or altered TFS cues (Oxenham and Simonson 2009;Freyman, Griffin, and Oxenham 2012). In addition, Füllgrabe, Moore, and Stone (2015) found no significant association between TFS sensitivity and a measure of dip listening for young and older normal-hearing (NH) listeners.…”
Section: Introductioncontrasting
confidence: 38%
“…Hopkins and Moore (2009), for example, observed an increase in MR with an increase in the number of spectral channels in which TFS cues were present. However, other studies have found no direct link between TFS cues and MR (e.g., Oxenham and Simonson, 2009;Bernstein and Brungart, 2011;Freyman et al, 2012). Recently, it has been suggested that MR arises in NH listeners due to a release from the random modulations present in nominally steady noise (e.g., Stone et al, 2012).…”
Section: Introductionmentioning
confidence: 99%